Influence of Procurement Key Performance Indicators on The Performance of State Agencies in Kenya - Ndemo, Bernard Mong'eri; Achuora, Dr. John; Achuora, Dr. John (International Journal of Supply Chain and Logistics, 2020)
Purpose: The purpose of the study was to examine influence of procurement key performance indicators on the performance of state agencies in Kenya with an aim of making recommendations on proper us Methodology: The study employed a descriptive research design, targeting the 127 heads of procurement in state agencies in Kenya, who were selected using simple random sampling, from the four strata. The researcher preferred this method because it allows an in-depth study of the subject. Data was collected using self-administered questionnaires. Structured questionnaires were used to collect data. Data was analyzed using descriptive and inferential statistics. Quantitative data was analyzed using multiple regression analysis. The qualitative data generated was analyzed by use of Statistical Package of Social Sciences (SPSS) version 22. The response rate of the study was 82%. Results and conclusion: The results indicate that there is a positive relationship (r=.509) between cost management and performance of state agencies in Kenya. In addition, the researcher found the relationship to be statistically significant at 5% level (p=0.000, <0.05). The results also indicate that there is a positive relationship (r=.398) between quality index management and performance of state agencies in Kenya. In addition, the researcher found the relationship to be statistically significant at 5% level (p=0.000, <0.05). The results indicate that there is a positive relationship (r=.678) between delivery management and performance of state agencies in Kenya. In addition, the researcher found the relationship to be statistically significant at 5% level (p=0.000, <0.05). The results indicate that there is a positive relationship (r=.685) between asset utilization management and performance of state agencies in Kenya. In addition, the researcher found the relationship to be statistically significant at 5% level (p=0.000, <0.05). Hence, it is evident that all the independent variables could explain the changes in implementation of performance of state agencies in Kenya, on the basis of the correlation analysis. The findings of the study indicated that cost management, quality index management, delivery management and asset utilization management have a positive relationship with performance of state agencies in Kenya Unique contribution to theory, practice and policy: Finally, the study recommended that public institutions should embrace procurement key performance indicators so as to improve performance and further researches should to be carried out in other public institutions to find out if the same results can be obtained